Heat Wave, Cone Crops, Forest-Floor Small Mammals, and Mustelid Predation in Coniferous Forests of Southern British Columbia - Thomas P. Sullivan; Druscilla S. Sullivan; Alan Vyse (Ecologies, 2025)
We report a landscape-scale natural experiment that followed the abundance and demography of forest-floor small mammals and the activity of small mustelids over a 4-year period of an extreme heat wave and abundant coniferous cone crops. Deer mice (Peromyscus maniculatus) and southern red-backed voles (Myodes gapperi) are major species in the coniferous forest-floor small mammal community near Summerland in southern British Columbia, Canada. Their major mammalian predators include the short-tailed weasel (Mustela richardsonii), long-tailed weasel (Neogale frenata), and American marten (Martes americana). We evaluated three hypotheses (H) that may explain the changes in these mammals from 2021 to 2024: (H1) that large coniferous cone crops in 2022 would have generated high populations of forest-floor small mammals in 2023 owing to enhanced reproductive output and overwinter survival; (H2) that increased activity of mustelids would have followed population increases, resulting in the decline of small mammal prey in 2024; and (H3) that the widespread occurrence of cone crops in 2022 would also have elicited the same mammalian responses in 2023 at a second study area (Golden, BC) 276 km and three mountain ranges from Summerland. During the summer periods of each year, small mammal populations were monitored by intensive live-trapping, and mustelid presence was measured via an index of activity based on live traps, fecal scats, and predation events. The mean abundance and reproductive performance of the P. maniculatus and M. gapperi populations increased in response to the coniferous seedfall, thereby supporting H1. The activity of small mustelids responded positively to increased numbers of small mammal prey and potentially acted in a regulatory and top–down function in these communities, and hence partially support H2. Similar responses at Summerland and Golden indicated that this seedfall event and changes in the mammalian community occurred at a landscape-scale, thereby providing partial support for H3. Potential differential effects of large seed crops on consumers did not affect the mean abundance patterns for P. maniculatus but apparently reduced this metric for M. gapperi. Heat waves, induced by anthropogenic climate change, may alter the frequency of coniferous masting events, and their effects may temporarily change the number and species of mammalian seed consumers and their predators.